EXPRESSION OF ENDOTHELIN-1 IN UNAFFECTED COLON MUCOSA 10CM AND 20CM FROM ADENOCARCINOMA OF THIS ORGAN - Stanojlović, Anja (Medicinski podmladak, 2025)
Introduction: Endothelin-1 is a vasoconstrictor peptide primarily synthesized by endothelial and smooth muscle cells. Increased expression of this peptide has been observed in inflammation, hypoxia, ischemia, various cardiovascular diseases and various types of cancer. In addition to vasoconstrictive, significant mitogenic, proangiogenic and anti-apoptotic effects have also been proven.The Aim: To examine the expression of endothelin-1 in the unaffected mucosa 10cm and 20cm away from colon adenocarcinoma and the lamina propria of the colon mucosa of healthy subjects.Material and Methods: The samples were obtained by biopsy at the Center for Gastroenterology, Clinical and Hospital Center "Dr. Dragiša Mišović-Dedinje" in Belgrade from patinets with malignant colon tumors. During the diagnostic colonoscopy, colon mucosa samples were taken 10cm and 20cm distal to the primary tumor lesion (n=10). A control group of samples (n=10) was obtained by endoscopic biopsy of the healthy subjects in the same institution. Immunohistochemical staining on paraffin samples was performed according to the established protocol. For statistical analysis of frequency, Fisher's exact probability test was used, using 2x2 contingency tables.Results: Statistically significant difference in the frequency of endothelin-1 expression was detected neither in the surface epithelium nor in the endothelial cells of the lamina propria of the colon mucosa at a distance of 10cm (p=0.38) or 20cm (p=0.67) from the tumor compared to the lamina propria of colon mucosa of healthy subjects. Also, no statistically significant difference was detected in the frequency of high and low expression of endothelin-1 in the epithelium and blood vessels of the lamina propria of the colon mucosa at a distance of 10cm and 20cm from the tumor (p=0.82)Conclusion: Endothelin-1 is variably expressed in the colon mucosa, predominantly by epithelial and endothelial cells. A statistically significant difference in the frequency of high and low expression of endothelin-1 between the groups was not detected.
Keywords: endothelin-1; colorectal adenocarcinoma; unaffected mucosa; human samples